2017
DOI: 10.1111/faf.12215
|View full text |Cite
|
Sign up to set email alerts
|

A comparative and evolutionary approach to oxidative stress in fish: A review

Abstract: Oxidative stress results from an imbalance between the production of reactive oxygen species and the antioxidants defences, in favour of the former. In recent years, the association between oxidative processes, environmental change and life histories has received much attention. However, most studies have focused on avian and mammalian taxonomic groups, with less attention given to fish, despite their ecological and socio‐economic relevance. Here we present a review of the extrinsic and intrinsic factors that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
158
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 312 publications
(168 citation statements)
references
References 169 publications
(216 reference statements)
4
158
2
4
Order By: Relevance
“…This supports a model in which older parents are more physiologically capable and resistant to oxidative stress, rather than a model where oxidative stress accumulates as a cost of ageing, reproduction or both. This finding is contrary to the commonly held view that oxidative stress accumulates with age (Birnie-Gauvin et al, 2017), and provides insight into physiological mechanisms behind the life-history tradeoff of reproductive male smallmouth bass.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…This supports a model in which older parents are more physiologically capable and resistant to oxidative stress, rather than a model where oxidative stress accumulates as a cost of ageing, reproduction or both. This finding is contrary to the commonly held view that oxidative stress accumulates with age (Birnie-Gauvin et al, 2017), and provides insight into physiological mechanisms behind the life-history tradeoff of reproductive male smallmouth bass.…”
Section: Resultscontrasting
confidence: 99%
“…Understanding if and how oxidative ecology is associated with different components of parental care and life-history decisions represents a significant knowledge gap, not just for smallmouth bass or teleost fish, but more broadly within parental care-providing vertebrates (Birnie-Gauvin et al, 2017;Costantini, 2016). We found that older, more experienced fish show reduced oxidative stress entering the parental care period.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Stressed fish have been demonstrated to be more vulnerable to disease because of impairment of the antioxidant defense systems (Velisek et al, 2011). To cope with oxidative damage, organisms have evolved a system to either prevent or repair the effects of oxidative stress (Birnie-Gauvin et al, 2017). Oxidative stress is caused by the formation of reactive oxygen species (ROS), H2O2, hydroxyl radicals, and superoxide anion radicals, which are the main by-products of oxidative metabolism and potentially cause cell damage (Azzi et al, 2004).…”
Section: Discussionmentioning
confidence: 99%